Rapid spread and high prevalence of the gall rust pathogen Uromycladium falcatariae in stands of Falcataria falcata - Neo Endra Lelana; Ujang Wawan Darmawan; Hani Sitti Nuroniah; Dwi Murti Puspitaningtyas; Ragil Setio Budi Irianto (Forest Science and Technology)
Gall rust disease, caused by the pathogenic fungus Uromycladium falcatariae, has become a serious concern in sengon (Falcataria falcata (L.) Greuter & R. Rankin) [syn. Falcataria moluccana (Miq.) Barneby & J.W. Grimes, Paraserianthes falcataria (L.) Nielsen], the third most important commercial forest tree in Indonesia. The aims of the study were to determine how far the pathogen could spread from the inoculum source. We hypothesized that spores disperse over short distances, leading to a gradual infection from the inoculum source. In 2016, a research plot (100 × 500 m) was established adjacent to a four-year-old sengon plantation infected by gall rust to serve as an inoculum source. Five observation plots were established at 100 m intervals from the inoculum source. Disease prevalence monitoring was conducted 1, 2, 4, and 7 years after tree planting. The study found that disease prevalence increased over time, regardless of proximity to the inoculum source. Gall rust infection naturally and rapidly occurred and the spread could reach at least 500 m from the gall rust inoculum source. In the first year of observations, more than 53% of the trees were infected with gall rust disease. Gradual infection within that distance did not occur. In fact, plant infection occurred simultaneously. Natural plant barriers are ineffective at preventing the spread of gall rust over distances of 500 m, indicating that teliospores may play a crucial role in disease dissemination.